If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + 4x = 7(x + -1) Reorder the terms: 11 + 4x = 7(-1 + x) 11 + 4x = (-1 * 7 + x * 7) 11 + 4x = (-7 + 7x) Solving 11 + 4x = -7 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 11 + 4x + -7x = -7 + 7x + -7x Combine like terms: 4x + -7x = -3x 11 + -3x = -7 + 7x + -7x Combine like terms: 7x + -7x = 0 11 + -3x = -7 + 0 11 + -3x = -7 Add '-11' to each side of the equation. 11 + -11 + -3x = -7 + -11 Combine like terms: 11 + -11 = 0 0 + -3x = -7 + -11 -3x = -7 + -11 Combine like terms: -7 + -11 = -18 -3x = -18 Divide each side by '-3'. x = 6 Simplifying x = 6
| 5z-9z=-7z-7-z | | 40=x(x+3) | | 2x+x/2+x+20=580 | | (5w+1)(2-w)=0 | | (1.5*b)*b=0 | | 1.5b*b=0 | | X*2=-9x-8 | | 3x-5-2x=5-12 | | 0.5(4x-2)= | | (5x-90)=2x+30 | | C-6c=0 | | (11r+6)(5r-4)=0 | | Y=0.6(100)+b | | 6n^2/2 | | x+13=5x | | 5(x)=5(2x-3) | | R=b^2+1 | | (5x)2=15x-45 | | 3c-1=c | | 3x-5-x=2x-3 | | 3ysquared= | | 3(2x+1)-2(3-2)=13 | | 15x-45/2=5x | | 1/3x3/8 | | (7a)x(2b)=0 | | 15/105 | | 9z+4-5z-5= | | -6(r-7)=-54 | | 8+9a=7 | | 4x+3+2y=11 | | 7x-4.23=0.2+2.57 | | 7x-4.23=0.2 |